Influence of blood viscosity on blood flow in the forebrain but not hindbrain after carotid occlusion in rats - Lenz, Christian; Frietsch, Thomas; Fütterer, Carsten Dietmar; Ackern, Klaus van; Kuschinsky, Wolfgang; Waschke, Klaus F. (Journal of cerebral blood flow & metabolism, 2000)
That cerebral blood flow remains unchanged at an increased blood viscosity, as long as the vascular supply is not compromised, was tested. To induce a reduced blood supply of some parts of the brain and to keep the supply unchanged in others both carotid arteries were occluded in anesthetized, ventilated rats. By this procedure, blood supply to the rostral brain, but not to the brainstem and cerebellum, was compromised. Blood viscosity was increased by intravenous infusion of 20% polyvinylpyrrolidone (high viscosity group) or decreased by infusion of 5% albumin (low viscosity group). Cerebral blood flow was measured by the [14C]iodoantipyrine method in 50 complete coronal sections of the rostral brain and 22 complete coronal sections of the brainstem and cerebellum in each rat. In the high viscosity group, mean cerebral blood flow of the rostral brain was significantly lower (46 ± 7 mL/100 g−1 · min−1) than in the low viscosity group (82 ± 18 mL/100 g−1 · min−1). No differences could be observed in brainstem and cerebellum between both groups (162 ± 29 mL/100 g−1 · min−1 vs. 156 ± 18 mL/100 g−1 · min−1). Local analysis of cerebral blood flow in different brain structures of the coronal sections showed the same identical results; i.e., in 29 of the 31 brain structures analyzed in rostral brain, local cerebral blood flow was lower in the high viscosity group, whereas no differences could be observed in the 11 brain structures analyzed in the brainstem and cerebellum. It is concluded that under normal conditions cerebral blood flow can be maintained at an increased blood viscosity by a compensatory vasodilation. When the capacity for vasodilation is exhausted by occlusion of supplying arteries, an increased blood viscosity results in a decrease of cerebral blood flow.